Responde Aí

Enunciado

Se

r ( u ,   v )   =   ( 1   -   u ) i   +   [ ( 1   -   u )   c o s   v ] j   +   [ ( 1   -   u )   s e n   v ] k

Então

∂ r ∂ u = _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _   e   ∂ r ∂ v = _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _  

Passo 1

Fala galera! Tudo tranquilo? Vamos fazer as derivadas!

Primeiro, r em relação a u :

∂ r ∂ u = ∂ ∂ u [ 1   -   u i   +   1   -   u c o s   v j   +   1   -   u s e n   v k ]

∂ r ∂ u = -   i -   c o s   v j -   s e n   v k

Agora, em relação a v :

∂ r ∂ v = ∂ ∂ v [ 1   -   u i   +   1   -   u c o s   v j   +   1   -   u s e n   v k ]

∂ r ∂ v = - 1   -   u s e n   v j   +   1   -   u c o s   v k

Beleza?? Só isso! 😊

Resposta

∂ r ∂ u = - i - c o s v j - s e n v k

∂ r ∂ v = - 1 - u s e n v j + [ 1 - u c o s v ] k